2009
DOI: 10.1590/s0001-37652009000300015
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and antitumor models of bioactive protective peptides

Abstract: Peptides are remarkably reactive molecules produced by a great variety of species and able to display a number of functions in uni-and multicellular organisms as mediators, agonists and regulating substances. Some of them exert cytotoxic effects on cells other than those that produced them, and may have a role in controlling subpopulations and protecting certain species or cell types. Presently, we focus on antifungal and antitumor peptides and discuss a few models in which specific sequences and structures ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 127 publications
2
31
0
3
Order By: Relevance
“…This entrance might lead to the disruption of the cell membrane accompanied by pore formation and/or changes on the cell membrane charge (Janek et al, 2013) and finally the interference with necrotic (Maher and McClean, 2008; Huang et al, 2011; Ausbacher et al, 2012; Wang et al, 2013a) and apoptotic pathways (Ausbacher et al, 2012). Pore formation is a mechanism associated to some AMPs and has been reported for ACPs as well (Rodrigues et al, 2009). The insertion of bulky hydrophobic amino acids on the cell membrane hydrophobic core with the acquisition of a stable structure can be the driving events for pore formation (Hilchie et al, 2011).…”
Section: Anticancer Peptides For Solid and Hematological Tumorsmentioning
confidence: 79%
See 1 more Smart Citation
“…This entrance might lead to the disruption of the cell membrane accompanied by pore formation and/or changes on the cell membrane charge (Janek et al, 2013) and finally the interference with necrotic (Maher and McClean, 2008; Huang et al, 2011; Ausbacher et al, 2012; Wang et al, 2013a) and apoptotic pathways (Ausbacher et al, 2012). Pore formation is a mechanism associated to some AMPs and has been reported for ACPs as well (Rodrigues et al, 2009). The insertion of bulky hydrophobic amino acids on the cell membrane hydrophobic core with the acquisition of a stable structure can be the driving events for pore formation (Hilchie et al, 2011).…”
Section: Anticancer Peptides For Solid and Hematological Tumorsmentioning
confidence: 79%
“…In a structural point of view, most ACPs have either α-helical or β-sheet conformation but some extended structures have already been reported (Hoskin and Ramamoorthy, 2008; Rodrigues et al, 2009; Wang et al, 2009a; Hammami and Fliss, 2010). Concerning cell targets, they can be classified into two major groups.…”
Section: Anticancer Peptides—classification Selectivity and Modes Omentioning
confidence: 99%
“…The 3D non‐acetylated anticancer peptide model presented cationic (Lys 3 ) and aromatic (Trp 2 ) residues forming a single amphipathic α‐helice that showed 55% of hydrophobic residues. This structural fold is commonly found in peptides with multiple activities such as antimicrobial, antifungal, and antitumoral [Rodrigues et al, 2009]. Helene and Maurizot [Helene and Maurizot, 1981] have observed that short oligopeptides containing basic and aromatic residues provided simple systems where it was possible to differentiate between single‐stranded and double‐stranded structures by inserting their aromatic residue between successive bases.…”
Section: Resultsmentioning
confidence: 99%
“…The primary function of defense peptides is to serve as naturally occurring antibiotics of the innate immune system, targeting a wide variety of microbes ranging from bacteria and viruses to parasites and fungi . However, over the last decade, it has become increasingly clear that many of these peptides also possess a potent ability to inactivate a wide range of cancer cells . A number of articles and databases have listed these anticancer peptides (ACPs), and inspection of these sources shows that the vast majority of ACPs are cationic and adopt molecular architecture that is either β‐sheet (β‐ACPs) or α‐helical (α‐ACPs), although several extended ACPs (E‐ACPs) have been described (Tables and ) .…”
Section: Defense Peptidesmentioning
confidence: 99%